Surface Charging on Insulating Films with Different Thicknesses in UPS - Lei Zhu; Xuefeng Xu (Applied Sciences, 2025)
The conventional view holds that ultraviolet photoelectron spectroscopy (UPS) measurements are not applicable to insulating materials due to interference from charging effects. To avoid surface charging, researchers typically restrict valence band structure investigations to ultra-thin films. However, the UPS spectral performance of ultra-thin films tends to correlate with the substrate characteristics and film thickness, while charging effects, which still unavoidably occur, can also affect the realism of the results. This study systematically investigates the charging effects and valence band structural evolution in SiO2 insulating films with controlled thickness variations through XPS and UPS depth profiling. By analyzing spectral shifts, surface potential dynamics, and work function variations, three continuous regimes are identified. The results demonstrate that the surface potential undergoes abrupt intensification when exceeding critical thickness thresholds (about 8 nm), a phenomenon governed by substrate resistivity and charge compensation pathways. Conventional work function determination methods remain valid only when the actual effect of the applied bias exceeds the surface potential values. For thicker films, the limited efficacy of negative bias fails to compensate for the spectral shifts caused by surface charging, consequently rendering work function measurements unreliable. These findings provide critical guidance for optimizing UPS measurements and spectral interpretation in insulating films.